Mathematical modeling skills in plane geometri - Ayi Darojat; Rima Rismawati; Usman Aripin (IKIP Siliwangi, 2026)
This study aims to analyze the process and responses of junior high school students to mathematical modeling in the context of plane figures, as well as to identify relevant solutions to improve these skills. This is particularly important to examine because, without a proper grasp of modeling, students tend to get stuck merely memorizing procedures without being able to translate real-world problems into mathematical language that leads to solutions. Modeling ability itself is a crucial competency that enables students to solve complex problems through simpler notational and symbolic representations. However, field observations indicate that students’ ability to solve geometric word problems remains weak due to difficulties in understanding problem contexts, performing mathematization, and a lack of understanding of formula procedures. Through a qualitative approach using tests and interviews with three eighth-grade students in Ciwidey, it was found that the first subject (S1) had moderate ability with challenges in the accuracy of illustrations and the interpretation of real-world solutions, while the second (S2) and third (S3) subjects were in the low category because they failed to understand the essence of the problem and were unable to solve the problems correctly. This research provides attention for teachers and researchers in developing students' mathematical modeling abilities, where in general students still experience difficulties in interpreting real-world problems into mathematical models